2012
DOI: 10.1259/bjr/98745548
|View full text |Cite
|
Sign up to set email alerts
|

LiverT1ρMRI measurement in healthy human subjects at 3 T: a preliminary study with a two-dimensional fast-field echo sequence

Abstract: Objectives: The aim of this study was to explore the technical feasibility of T 1 r MRI for the liver, and to determine the normal range of liver T 1 r in healthy subjects at clinical 3 T. Methods: There were 15 healthy volunteers. Three representative axial slices were selected to cut through the upper, middle and lower liver. A rotary echo spin-lock pulse was implemented in a two-dimensional fast-field echo sequence. Spin-lock frequency was 500 Hz, and the spin-lock times of 1, 10, 20, 30, 40 and 50 ms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 32 publications
2
73
0
Order By: Relevance
“…Liver signal intensity decreases upon the withdrawal of CCl 4 insult, and returns to the baseline value at week 4 post CCl 4 withdrawal out healthy volunteer liver T1ρ MR measurements. We found that when two readers measured the same ten volunteers' MR images, the inter-reader reproducibility (ICC) was 0.955; and with the ten subjects imaged twice, the ICC for reproducibility of repeat MR examinations was 0.764, suggesting the clinical applicability of liver MR T1ρ technique [41].…”
Section: Discussionmentioning
confidence: 92%
“…Liver signal intensity decreases upon the withdrawal of CCl 4 insult, and returns to the baseline value at week 4 post CCl 4 withdrawal out healthy volunteer liver T1ρ MR measurements. We found that when two readers measured the same ten volunteers' MR images, the inter-reader reproducibility (ICC) was 0.955; and with the ten subjects imaged twice, the ICC for reproducibility of repeat MR examinations was 0.764, suggesting the clinical applicability of liver MR T1ρ technique [41].…”
Section: Discussionmentioning
confidence: 92%
“…A number of MR imaging techniques have been investigated to assess early liver parenchyma fibrosis, including T 1 rho imaging [27-31], tagged MRI assessing liver strain [32], MR elastography [33, 34] and intravoxel incoherent motion (IVIM) technique [35, 36]. Our current study for the first time demonstrated the feasibility and evaluated the reproducibility of CEST imaging of in-vivo liver at the clinical field strength of 3T in both rats and human.…”
Section: Discussionmentioning
confidence: 99%
“…A total of approximately 15 ROIs were obtained each liver, and the mean value of these 15 ROIs was regarded as the value of the liver T1ρ. The inter-and intra-reader reproducibility for ROI placement has been shown to be excellent in past studies (7,8) [more details of the ROI placement are shown in supplement document of reference (7)]. …”
Section: Methodsmentioning
confidence: 99%
“…Despite the biophysical mechanism has not been fully illuminated, recently Wang et al and Zhao et al described the usefulness of T1ρ MR imaging for assessment in rat liver fibrosis models, with the increase of T1ρ value correlated severity of fibrosis. Studies in human subjects, both in healthy volunteers and liver fibrosis patients, soon followed (7)(8)(9)(10)(11)(12)(13)(14)(15). In a group of 25 healthy volunteers and 35 cirrhosis patients, Allkemper et al (11) reported that T1ρ values did not correlate with necroinflammatory activity, degree of steatosis or presence of iron load, but it was significantly associated with the ChildPugh staging of the patients.…”
Section: Original Articlementioning
confidence: 99%